Social Support for Minors in the First Period of Great Patriotic War - Roman S. Serebryaniy; Denis V. Kamelskikh; Oksana V. Yaremchuk ("Paediatrician" Publishers LLC, 2022)
This article presents a narrative that reveals the state of life and health of children in the first months of the Great Patriotic War. Special place goes to the analysis of archival documents indicating the distressful situation of evacuated children, faced unsanitary conditions, lack of food, and difficulties with settling in new places of residence. The activity of the Council of People's Commissars of the USSR, the People's Commissariat of Health of the USSR and the RSFSR on carrying out measures of social support for minors in the first period of the Great Patriotic War is presented. The maximum possible conditions for the protection of minors' health were implemented as consequence of the execution of orders on places. Difficulties with the implementation of measures for the arrangement of evacuated children in various regions of the country are described depending on local resources and taken measures efficacy (Tula, Ryazan, Yaroslavl, Kuibyshev regions). The ongoing activities are clearly illustrated by the example of the work of the Middle Volga Institute for the Protection of Motherhood and Infancy.